PENGUATAN LEMBAGA ADAT “KEWANG” DALAM KONSERVASI SUMBER DAYA ALAM DI DESA HARUKU - Sahureka, Mersiana; Sahupala, Andjela (Universitas Pattimura, 2023)
Kewang is one of the Customary Institutions whose function is to regulate the use and protection of natural resources both on land and at sea. The role of the Kewang Customary Institution in Haruku is maximally related to the function of supervision/controlling of community activities convert the mangrove forest ecosystem which is the lompa fish habitat. In addition to the activities of the people who hunt and take eggs from scorched birds freely. The goals to be achieved from Community Service activities carried out in Haruku country are 1. Rehabilitation of mangrove forest ecosystems as lompa fish (Trisina baelama) habitat, 2. Improving partners' abilities and skills in carrying out mangrove cultivation techniques, 3. Increasing partner supervision on the presence/population of gosling birds. The method used to transfer science and technology is 1). Preparation, 2). The implementation stage consists of: counseling and training, procuring mangrove seeds/saplings and making nurseries, planting, making scorched bird breeding cages, carrying out maintenance of mangrove plants that have been planted in the field and at the nursery location. The results achieved in this activity were making nurseries and planting 1000 mangrove saplings, building 2 bird brooding cages, cleaning the beach, counseling on mangrove cultivation and nursery techniques, the Role of Indigenous Institutions in the Management of Natural Resources, Breeding of rare fauna.